Phyllis Greenacre papers - Greenacre, Phyllis
Correspondence, writings, and other material relating to Greenacre's psychoanalytic career. Includes material pertaining to psychoanalytic theory and practice and to organizations including the American Psychoanalytic Association, the International Psycho-Analytical Association, and the New York Psychoanalytic Institute. Includes drafts of her unpublished study of H.C. Anderson. Correspondents include Simon A. Grolnick, Marjorie Harley, Selma Kramer, Ernst Kris, J. Moussaieff Masson, Jerome D. Oremland, and Albert J. Solnit.
Psychoanalyst, psychiatrist, educator, and author. Born 1894; died 1989.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Andersen, H. C. -- 1805-1875.; Grolnick, Simon A., -- 1930- -- Correspondence; Harley, Marjorie -- Correspondence; Kramer, Selma -- Correspondence; Kris, Ernst, -- 1900-1957 -- Correspondence; Masson, J. Moussaieff -- 1941- -- Correspondence; Oremland, Jerome D. -- Correspondence; Solnit, Albert J. -- Correspondence; American Psychoanalytic Association; International Psycho-Analytical Association; New York Psychoanalytic Institute; Psychoanalysis; Psychoanalysis -- Societies, etc; Authors; Educators; Psychiatrists; Psychoanalysts